X-Linked Alport Syndrome in Women: Genotype and Clinical Course in 24 Cases - Mastrangelo, Antonio; Giani, Marisa; Groppali, Elena; Castorina, Pierangela; Soldà, Giulia; Robusto, Michela; Fallerini, Chiara; Bruttini, Mirella; Renieri, Alessandra; Montini, Giovanni (Frontiers in Medicine, 2020)
OBJECTIVES X-linked Alport syndrome (XLAS) females are at risk of developing proteinuria and chronic kidney damage (CKD). The aim of this study is to evaluate the genotype-phenotype correlation in this rare population. MATERIALS and METHODS This is a prospective, observational study of XLAS females, confirmed by a pathogenic mutation in the COL4A5 and renal ultrastructural evaluation. Proteinuria, renal function and extrarenal involvement were monitored during follow-up. Patients were divided in 2 groups, according to mutations in COL4A5: missense (Group 1) and non-missense variants (Group 2). RESULTS Twenty-four XLAS females, aged 10.6±10.4 years at clinical onset (mean follow-up: 13.1±12.6 years) were recruited between 2000 and 2017 at a single centre. In group 1 there were 10 patients and in group 2, 14 (mean age at the end of follow-up: 24.9±13.6 and 23.2±13.8 years, respectively). One patient of group 1 and 9 of group 2 (p<0.05) developed proteinuria during follow-up. Mean eGFR was lower in Group 2 (p<0.03), where two patients developed CKD. No differences on hearing loss were documented among the two groups. Two patients in Group 2 carried one mutation in both COL4A5 and COL4A3 (digenic inheritance) and were proteinuric. In one family, the mother presented only hematuria while the daughter was proteinuric and presented a greater inactivation of the X chromosome carrying the wild-type allele. CONCLUSIONS The appearance of proteinuria and CKD is more frequent in patients with S variants. Carrying digenic inheritance and skewed XCI seem to be additional risk factors for proteinuria in XLAS females.